2003
DOI: 10.1093/fampra/20.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing home visits in Slovenian general practice

Abstract: It is possible to use the questionnaire developed by EGPRW on a national scale and to obtain representative valid national data. The home visiting rate in Slovenia is low compared with rates in other countries. Rural location of practice, GP's age, trainee status and the number of older patients on the list are the most important predictors of the home visiting rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Although most international studies reveal higher home visiting rates for experienced GPs [2] in our sample the younger doctors conducted many more house calls than their older colleagues -probably because German practice owners tend to delegate home visits to their vocational trainees. Svab et al (2003) reported a similar trend in the Slovenian primary health care system of young residents losing their interest in home visits after completing their training [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Although most international studies reveal higher home visiting rates for experienced GPs [2] in our sample the younger doctors conducted many more house calls than their older colleagues -probably because German practice owners tend to delegate home visits to their vocational trainees. Svab et al (2003) reported a similar trend in the Slovenian primary health care system of young residents losing their interest in home visits after completing their training [9]. …”
Section: Discussionmentioning
confidence: 99%
“…GPs have to pay most of their home visits out of regular office hours, without extra payment, which could be the reason for very small proportion of home visits compared with other countries in Europe [18].…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 99%
“…The process of organizing HCS varies among different countries depending on their health systems. However, some challenges show similarities among different settings: such as medically challenging home environments, time constraints, difficulties experienced during consultation and planning of requests (12,17).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…To the best of our knowledge, however, no qualitative studies have examined the experience of HCS delivery in Turkey. Our literature search revealed some quantitative (10)(11)(12)(13)(14)(15)(16) and qualitative studies (17)(18)(19)(20)(21)(22) dealing with different aspects of HCS. Several quantitative studies from Turkey are also available (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%